2021
DOI: 10.3390/jcs5080215
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Tribological Attributes of Al-CNT-Sn Composites Prepared by Press and Sintering

Abstract: Carbon nanotubes (CNTs) have shown tremendous progress during the past two decades due to their extraordinary properties. With CNTs added as an alloying element, various engineering materials exhibit better mechanical properties. Multi-walled carbon nanotubes (MWCNT) were synthesized in-house by chemical vapor deposition process. Carbon nanotube-reinforced aluminum composites were prepared by cold pressing (or compaction) and sintering using different fractions (0.5, 1.0, 1.5, and 2.0 weight percent) of MWCNTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…15 Dhore et al investigated the mechanical and tribological properties of Al-CNTs-tin nanocomposites and the samples were fabricated by the pressing and sintering technique. 16 They found that the hardness and wear resistance of the nanocomposite improved with the amount of CNTs. Chen and Kondoh developed a consolidation technique for the synthesis of CNTs-Al composites and concluded that the addition of CNTs could decrease the sintering ability of nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…15 Dhore et al investigated the mechanical and tribological properties of Al-CNTs-tin nanocomposites and the samples were fabricated by the pressing and sintering technique. 16 They found that the hardness and wear resistance of the nanocomposite improved with the amount of CNTs. Chen and Kondoh developed a consolidation technique for the synthesis of CNTs-Al composites and concluded that the addition of CNTs could decrease the sintering ability of nanocomposites.…”
Section: Introductionmentioning
confidence: 99%